Evaluation two years after laparoscopic promontory fixation with titanium for vaginal vault prolapse - Avila, Carla (2015)
Objectives: To determine efficacy of laparoscopic promontory fixation with mesh and titanium helicoidal fixation in the treatment of vaginal vault prolapse, and to describe self reported health status. Design: Descriptive, transversal study. Setting: Gynecology service, Hospital Alberto Sabogal Sologuren, EsSalud, Lima, Peru. Participants: Patients with diagnosis of vaginal vault prolapse treated by laparoscopy. Interventions: Clinical charts of five of eight patients con diagnosis of vault prolapse repaired by laparoscopic promontory fixation with mesh and helicoidal titanium fixation from January 2008 through September 2008. Patients were examined two years after urgery and evaluated by analogical visual scale that included four health dimensions and possibility of three answer alternatives related to quality of life following surgery. Main outcome measures: Correction of vault prolapse and improvement of quality of life. Results: Mean age was 67,2 years, parity 4. Prolapse was corrected in 60% (3/5); another 60% (3/5) presented mild difficulties in daily activities, 20% (1/5) severe problems related to sexuality, 60% (3/2) mild vaginal pain, and 80% (4/5) mild depression, basically due to delay in institutional attention. Conclusions: Cure was less than expected. Need of more  exhaustive follow-up of patients to solve related problems is emphasized.